Significance of the study of sedimental rock-forming evolution in the Earth history for the reconstruction of the changes of geochemical settings on its surface - V. G. Kuznetsov (Известия высших учебных заведений: Геология и разведка, 2019)
The distribution in the geological section of two groups of sedimentary rocks, siliceous and carbonate rocks of different composition — has been examined. Acid-base conditions of external geospheres have been reconstructed in consideration of the peculiar conditions of the formation of rocks of different material composition. The acidic environments have been shown to be such conditions in the Archean period, the alkaline environments — in the Proterozoic, and slightly alkaline — in the Phanerozoic. At the same time, in the Archean the weathering was purely chemical, prebiogenic, which determined the intense removal of iron and silica from the basic igneous rocks that covered the surface of the early Earth. The emergence of cyanobacterial photosynthesizing communities, utilization of carbon dioxide led to the change to alkaline environment, which determined the accumulation of magnesites and dolomites. The diverse biota of the Phanerozoic caused the formation of pH values close to modern. The mechanisms and forms of the deposition of carbonate and siliceous materials changed alongside with the evolution of life.